Acceptance based telephone support around the time of transition to secondary progressive multiple sclerosis: a feasibility randomised controlled trial - Meek, Christopher (2020)
Introduction: Multiple Sclerosis (MS) is the most common neurological disease in young adults, and it contains different stages. Transitioning to Secondary Progressive Multiple Sclerosis (SPMS) is a difficult time for patients, fraught with psychological uncertainty and an increase in physical disability. In parallel, healthcare appointments become less frequent, disease modifying treatments are withdrawn, and social contacts typically become more difficult to maintain. The aim of this study was to assess whether providing a brief, Acceptance and Commitment Therapy (ACT) based telephone supported bibliotherapy intervention during transition to SPMS is feasible, effective and valued by participants. A separate questionnaire study was conducted as an adjunct to the project to determine the strength of relationship between psychological flexibility and distress in SPMS.